Functional‐DNA‐Driven Dynamic Nanoconstructs for Biomolecule Capture and Drug Delivery. Issue 45 (30th July 2018) - Kim, Jinhwan; Jang, Donghyun; Park, Hyeongmok; Jung, Sungjin; Kim, Dae Heon; Kim, Won Jong
Abstract: The discovery of sequence‐specific hybridization has allowed the development of DNA nanotechnology, which is divided into two categories: 1) structural DNA nanotechnology, which utilizes DNA as a biopolymer; and 2) dynamic DNA nanotechnology, which focuses on the catalytic reactions or displacement of DNA structures. Recently, numerous attempts have been made to combine DNA nanotechnologies with functional DNAs such as aptamers, DNAzymes, amplified DNA, polymer‐conjugated DNA, and DNA loaded on functional nanoparticles for various applications; thus, the new interdisciplinary research field of "functional DNA nanotechnology" is initiated. In particular, a fine‐tuned nanostructure composed of functional DNAs has shown immense potential as a programmable nanomachine by controlling DNA dynamics triggered by specific environments. Moreover, the programmability and predictability of functional DNA have enabled the use of DNA nanostructures as nanomedicines for various biomedical applications, such as cargo delivery and molecular drugs via stimuli‐mediated dynamic structural changes of functional DNAs. Here, the concepts and recent case studies of functional DNA nanotechnology and nanostructures in nanomedicine are reviewed, and future prospects of functional DNA for nanomedicine are indicated. Abstract : Functional DNA or functional‐DNA‐driven nanostructures are used in various biomedical applications owing to their high programmability, predictability, and biocompatibility. Functional DNA and nanostructures for nanomedicine are reviewed with various case studies, and future prospects of future nanomedicine based on functional DNA nanotechnology is suggested.